Development of Ecofriendly Corrosion Inhibitors for Application in Acidization of Petroleum Oil Well. (23rd October 2012) - Yadav, M.; Kumar, Sumit; Yadav, P. N.
Abstract : In the present investigation the protective ability of 1-(2-aminoethyl)-2-octadecylimidazoline (AEODI) and 1-(2-octadecylamidoethyl)-2-octadecylimidazoline (ODAEODI) as corrosion inhibitors for N80 steel in 15% hydrochloric acid has been studied, which may find application as ecofriendly corrosion inhibitors in acidizing processes in petroleum industry. Different concentration of synthesized inhibitors AEODI and ODAEODI was added to test solution (15% HCl), and corrosion inhibition of N80 steel was tested by weight loss, potentiodynamic polarization, and AC impedance measurements. Influence of temperature (298 to 323 K) on the inhibition behaviour was studied. Surface studies were performed by using SEM. It was found that both the inhibitors were effective inhibitors, and their inhibition efficiency was significantly increased with increasing their concentration. Polarization curves revealed that the used inhibitors represent mixed-type inhibitors. The adsorption of used inhibitors led to a reduction in the double-layer capacitance and an increase in the charge transfer resistance. The adsorption of used compounds was found to obey Langmuir isotherm. The adsorption of the corrosion inhibitors at the surface of N80 steel is the root cause of corrosion inhibition.